Adsorption of chia proteins at interfaces: Kinetics of foam and emulsion formation and destabilization - López, Débora Natalia (2019)
Chia proteins were extracted by solubilisation at pH 10 or 12 and precipitated at pH 4.5. Isolates were named as CPI10 and CPI12, according to their extraction pH, 10 or 12, respectively. The surface properties of both isolates were studied at neutral conditions. Foams were formed by air bubbling and both the formation and destabilization processes were analysed by conductimetry. The extraction pH significantly affected the interfacial properties of chia proteins. The higher surface hydrophobicity in CPI10 led to more flexible proteins with improved foaming properties. Foams formed by CPI10 were more stable than those by CPI12 due to the formation of a thicker interfacial film, which meant a greater ability to retard liquid drainage. Freshly-made coarse emulsions stabilized with CPI12 showed a lower mean droplet size and a significantly lower degree of overall destabilization than those stabilized with CPI10. None of the two emulsions showed flocculating effect.